Mode of Delivery Does Not Influence Postpartum Hypercoagulability Measured by Thrombin Generation or Thromboelastometry - Guimicheva, Boriana; Roberts, Lara N.; Patel, Jignesh P.; Subramanian, Devi; Arya, Roopen (TH Open, 2020)
Introduction Venous thromboembolism (VTE) is a significant cause of maternal mortality with the greatest risk postpartum. Mode of delivery influences VTE risk, with emergency caesarean section (CS) associated with the highest risk (CS). Thromboprophylaxis is recommended for selected women to reduce the risk of VTE.We aimed to investigate the impact of mode of delivery and thromboprophylaxis on hypercoagulability as measured by thromboelastometry (TEM) and thrombin generation (TG) in women at high VTE risk.Materials and Methods Blood was collected from 99 pregnant women with VTE risk factors at up to five time points from pre- (T1) and post (T2)-delivery to 6 weeks postpartum (T5). Multiple linear regression was utilised to compare TG and TEM between those with vaginal delivery (VD) and CS at each time point. Paired sample t-test with post hoc Bonferroni correction was utilised to compare laboratory markers over time.Results Women in both groups had a median of three postpartum VTE risk factors, with higher body mass index and parity post-VD. In both the groups, TG and TEM parameters suggested hypercoagulability at T2 compared with T1, with resolution at T5. There were minimal differences between groups, apart from T2 with shorter clot formation time and higher maximum clot firmness in the VD group.Conclusion TG and TEM illustrate hypercoagulability associated with pregnancy and delivery. The pattern of postpartum hypercoagulability seen in women with VTE risk factors was similar irrespective of mode of delivery. Further research is required to establish the effect of labour on TG/TEM in the absence of low molecular weight heparin use.
Keywords: enoxaparin; vaginal delivery; caesarean section; thrombin generation; thromboelastometry